Analysis and Design of Sales Information System on Web-Based E-Commerce in Yoga Farm Catfish Breeding Business Using UML - Cahyo, Muhamad Ridho Dwi; Candiwan, Candiwan (STMIK Budi Darma, 2020)
Yoga Farm is a Micro, Small, and Medium Enterprises (MSME) that focuses on catfish breeding that is still doing business processes manually. With this process, information received by related parties is very difficult to obtain quickly. Therefore, the product is still not widely known, and customers are still few because the system used in sales and promotions still uses a manual system. The research method used is qualitative. This study aims to create a sales information system recommended at Yoga Farm and design using Unified modeling language (UML) for the recommended business processes. Customers will get product information in real-time, products can be widely recognized, and the number of Yoga Farm customers can increase. Based on the results of this study, adoption of a web-based sales information system can certainly make it easier to get the latest information quickly, can expand the market and can also facilitate customers in the transaction. For future research, this research can be used as a reference for conducting similar studies at other MSMEs to increase sales